REVISION OF TERRITORIAL SCHEMES OF SOLID MUNICIPAL WASTE MANAGEMENT: SEARCH FOR SOLUTIONS - N. Musinova (Publishing House of the State University of Management, 2018)
Solid municipal waste as part of production and consumption waste occupy a small share. However, the volume of their burial in Russia is growing rapidly, while in many countries they are signicantly reduced. In 2016, the monitoring of the progress in reforming the sphere of waste management revealed, in particular, that many subjects of the Russian Federation violated the regulatory terms for the development of territorial schemes. In the result the decision on the postponement of the start of activities of the regional operators by 1 January 2019. This article describes the territorial schemes of treatment of solid municipal waste at the stage of their revision and attempts to analyze them from the position of compliance with the General principles of reform of the sphere of waste management.